MENGKAJI ULANG KONSEP KEWARGANEGARAAN, KEBANGSAAN, DAN ETNISITAS - Haryo Ksatrio Utomo, M. IP (Universitas Bung Karno, 2021)
AbstractThis article discusses the theoretical discourse of political identity. The discussion of the article focuses specifically on citizenship, nationality, and ethnicity. These three things limit this article for two reasons. First, social conflicts are often closely related to claims of